TRANS-ASIAN TECTONIC MEGA-BELT: ITS PRINCIPAL CHARACTERISTICS AND METALLOGENY - Chen B.W.; Chen T.Y. (My University, 2007)
The vast area between the Siberia Platform in the north and the Sino-Korean and Tarim platforms in the south is called The Trans-Asian Tectonic Mega-Belt (TATMB) in this paper. In consideration of geological history and tectonic settings, the mega-belt can be divided into (1) Altay-Sayan-Mongolia-Okhotsk belt, (2) Balkhash-Hinggan belt, and (3) Ural-South Tianshan belt. The Altay-Sayan-Mongolia-Okhotsk belt takes the Mid-Mongolian Tectonic Lines (MMTL) as its southern boundary, the Ienissei-Muya fracture, Baikal fracture and south Stanov fracture as its northern boundary, adjacent to the Siberian Platform. The Balkhash-Hinggan belt is situated in the south of MMTL; the so-called Nikolayev Line and the northern marginal fracture of the South Tianshan Mountains constitute the western section of its southern boundary, while the eastern section of the southern boundary follows the thrust on the northern margin of the Sino-Korean Platform. The Balkhash-Hinggan belt could be subdivided into the Balkhash-Junngar -North-Middle Tianshan-Inner Mongolia-Xilinhot zone in the south and Zaisan-Ertix-South Mongolia-Great Hingganling Zone in the north. The Ural-South Tianshan belt extends from Xinjiang of China through Central Asia up to the Urals. Archean and Paleoproterozoic crystalline basements were developed in the Siberia Platform as well as in the Sino-Korean and Tarim platforms. Sedimentary covers began to develop in Mesoproterozoic, and break-up on the margin of the block took place in early Mesoproterozoic. In contrast, no sedimentary cover of Meso-Neoproterozoic was observed to lie unconformably over the old crystalline basements, nor direct evidence of the break-up of the crust was found. In some places, Cambrian strata were continuous to late Neoproterozoic strata. Paleozoic saw the development of marine eruptive rocks of various kinds, which included volcanic rocks on passive continental margin, volcanic rocks developed on island arc and eruptives on oceanic crust, etc. The Trans-Asian Tectonic Mega-Belt showed a movement and assemblage face to face of the Siberian Platform in the north and the Sino-Koran and Tarim platforms in the south. The development began approximately in Neoproterozoic, was proceeding mainly in Paleozoic and ended in Mesozoic. From Triassic on, this mega-belt entered into an active period of the western Pacific margin. In view of metallogeny, this mega-belt may be subdivided into corresponding tectono-metallogenic belts as follows: (1) Altay-Sayan-Mongolia-Okhotsk belt, including a) Altay-Sayan zone, and b) Mongolia-Okhotsk zone; (2) Balkhash-Hinggan belt, including a) Zaisan-Ertix-South Mongolia-Great Hingganling zone and b) Balkhash-Junggar-North-Middle Tianshan-Inner Mongolia-Xilinhot zone; (3) South Tianshan zone. The main minerals include Au, U, Ag, Cu, Mo, Pb and Zn, W, Sn, Rare metals, Fe, Ni, mica, gems, fluorite, graphite, magnesite, zeolite, etc. The mineralization in the mega-belt was mainly related to magmatism and hydrothermal activities of Paleozoic, while the most important mineralization in the Mongolia-Okhotsk zone took place in Mesozoic.
Keywords: METALLOGENY; PRINCIPAL CHARACTERISTICS; TRANS-ASIAN TECTONIC MEGA-BELT